Stratificazioni della mobilità. L’impatto del turismo a Exarchia, Atene - Anna Giulia Della Puppa (Archivio Antropologico Mediterraneo)
This article examines the urban transformations of the Exarchia neighborhood in Athens, focusing on the long-standing processes of mobility and spatial reconfiguration that have shaped it. Since its founding by Cycladic laborers in the 19th century, the neighborhood has been characterized by intense social dynamism, gradually becoming home to a wide range of both temporary and permanent residents. Over time, it established itself as a student and cultural hub, particularly during the resistance and in the aftermath of the military dictatorship (1967-1974). Exarchia developed a model of dwelling rooted in networks of solidarity and flexible forms of inhabitation. During and after the “long summer of migration” in 2015 (Kasparek, Speer 2015; Rozakou 2020), these practices intersected with the life trajectories and needs of newly arrived populations, who contributed to the redefinition of living and social spaces through self-organized initiatives and informal housing arrangements. Today, Exarchia is undergoing a profound transformation, as increasing tourism pressure and real estate speculation progressively erode its social fabric, subordinating it to market-driven logics.